THE PERFORMANCE MEASUREMENT OF CONSULTING SERVICE COMPANY IN INDONESIA; CASE STUDY - Wahyu Ismail Kurnia; Ariamin Ariamin; Elisa Kusrini (Journal of Industrial Engineering Management, 2021)
Performance evaluation is the first step of a company in reaching its competitive advantage in the midst of globalization and free market enactment. The result of performance evaluation can be used as strategic formulation and decision making in fixing performance indicator which is considered as poor. From the facts, this research uses the evaluation adopted from PwC, which used to evaluate the performance of a consulting service company in Indonesia named XYZ Ltd. The reason for choosing PwC business model is because it covers all aspects that affect company’s ability to achieve competitive advantage. Moreover, this research uses 5 of 7 aspects of performance measurement offered by PwC business model. Measurement indicators and characteristics based on library research and company’s internal managerial party interviews are made, so that the evaluation process can be interpreted into the formulation of strategic improvement and decisions making. The result of performance measurement is expected to be able to give a new perspective in overall performance evaluations of consulting companies and evaluate company’s ability to win over its competitors, as well as to prove the ability of PwC’s measurement model in evaluating the performance of consulting companies in Indonesia model of performance.